A Comparative Study of Nanoparticle-Ink-Based CIGSSe Thin Film Solar Cells on Different Back Contact Substrates - Park, Se Jin; Cho, Jin Woo; Park, Gi Soon; Jeong, Jae Seung; Kim, Jihyun; Ko, Doo-Hyun; Hwang, Yun Jeong; Min, Byoung Koun (WILEY-V C H VERLAG GMBH, 2016)
The effect of the back contact electrode in nanoparticle-ink-based CIGSSe solar cells was investigated using different glass substrates with either a fluorine-doped SnO2 (FTO) conducting layer or a molybdenum (Mo) conducting layer. The morphologies, crystal structures, and compositional distributions of the Cu(In (x) Ga1- (x) )(S (y) Se1- (y) )(2)(CIGSSe) films are very similar in spite of the different back contact materials. The observed performances of the solar cell device, however, are somewhat different. The device that was fabricated on the FTO back contact substrate revealed a lower open-circuit voltage ( V (oc)) and fill factor (FF) than the Mo back contact substrate, resulting in lower solar cell efficiencies (6.5% for FTO and 7.4% for Mo). The differences between the behaviors are attributed to the interfacial properties between the CIGSSe film and the back contact electrode.
Keywords: LOW-COST; PRECURSORS